Cost-Benefit Analysis of Modern Vegetable Farming in Bhaktapur DistrictSurya Prasad Poudel - Tara Prasad Adhikari (Management Dynamics, 2024)
Modern vegetable farming presents a promising solution to the challenges facing traditional agriculture in Nepal, including low productivity, unsustainable input use, and environmental vulnerability. Despite its potential, adoption remains limited, especially in peri-urban districts like Bhaktapur. This study aims to assess the economic viability of modern farming methods for three high-value vegetables: tomato, cauliflower, and radish. The research employed a Cost-Benefit Analysis (CBA) framework to evaluate profitability using Net Present Value (NPV) and Benefit-Cost Ratio (BCR) indicators. Primary data were collected from 25 farmers in Madhyapur Thimi and Suryabinayak through structured surveys and field observations. Sensitivity analyses were conducted to assess how variations in price, cost, and yield affected profitability under modern farming systems. Findings revealed that all three crops were profitable, with cauliflower achieving the highest BCR (4.12) and NPV (NPR 525,940), followed by tomato and radish. Cauliflower demonstrated the greatest resilience to cost and yield fluctuations. Tomato had the highest gross income but required the largest investment. Radish, while profitable, was more sensitive to input cost and market price changes, making it less stable in adverse conditions. The results confirm the economic advantage of modern vegetable farming and support prior studies advocating for improved agricultural techniques. However, the underutilization of these methods in Bhaktapur suggests structural and informational barriers that need addressing. This study provides localized evidence supporting the promotion of modern vegetable farming in Nepal. Policy support in the form of subsidies, credit access, training, and market infrastructure is essential to scale adoption. Future research should explore behavioral and institutional factors influencing technology uptake among farmers.